Monitoring the Condition of the Natural and Economic Use of Land in the Poltava Region - Shchepak Vera V. (Bìznes Inform, 2017)
The article is aimed at monitoring the condition of the natural and economic use of land on the basis of methods for integrated evaluation as well as determining the levels of intensity of land use at the regional level. Various views on evaluation of the condition of land have been considered. As the main attributes of the intensity of land use were accepted the agro-landscape ecological stability, the anthropogenic load, the ploughness of territory, the ploughness of agricultural land, the agricultural development of territory, and the recreational capacity. On the basis of methods for integral evaluation both the subjective and the objective importance of attributes has been determined, the integral indicators of intensity of land use have been calculated. Three levels of intensity of natural and economic use of land in the districts of Poltava region have been allocated, boundaries of the quantitative values of indicators have been determined. Prospect for further research is to evaluate the intensity of natural and economic land use at the national level in order to define a strategy for the rational use and protection of land in Ukraine and to formulate the directions of development of the regional land use on the basis of system approach.